(untitled) (KULT_online, 2019)
Departing from traditional figurations of the male traveler-explorer, Ingrid Horrocks’s Women Wanderers and the Writing of Mobility, 1784-1814 analyzes women writers’ thematic as well as formal representations of the ‘reluctant woman wanderer’ figure. Situating the writings of Charlotte Smith, Ann Radcliffe, Mary Wollstonecraft, and Frances Burney in the larger context of mobility and sympathy studies, Horrocks emphasizes two important gendered privileges unavailable to the majority of women: traveling as a liberating quest for individual identity and sympathy as an ethical product of detached observation. As Horrocks meticulously illustrates the absence of sympathy or freedom in a woman’s painfully endless movement, she sheds light on not only women’s social and psychological status in late-eighteenth-century Britain but also the role of traveling in British literature at large.